Identification of two rare NPRL3 variants in two Chinese families with familial focal epilepsy with variable foci 3: NGS analysis with literature review - Hu, Junji; Gao, Xueping; Chen, Longchang; Kan, Yuling; Du, Zhaoli; Xin, Shuangqing; Ji, Wenkai; Yu, Qiang; Cao, Lili (Frontiers in Genetics, 2023)
Background: The GAP Activity Towards Rags 1 (GATOR1) complex, which includes DEPDC5, NPRL2, and NPRL3, plays a key role in epilepsy. It has been reported that focal epilepsy is associated with mutations in the NPRL3 gene in some cases. We report two rare mutations in the NPRL3 gene in two unrelated Chinese families with focal epilepsy in this study. Methods: The proband and her brother in family E1 first experienced seizures at 1.5 and 6 years of age, respectively. Despite resection of epileptogenic foci, she still suffered recurrent seizures. The first seizure of a 20-year-old male proband in family E2 occurred when he was two years old. To identify pathogenic variants in these families, whole-exome sequencing (WES) was performed on genomic DNA from peripheral blood. Results: In family E1, the trio-WES analysis of the proband and her brother without apparent structural brain abnormalities identified a heterozygous variant in the NPRL3 gene (c.954C>A, p.Y318*, NM_001077350.3). In family E2, the proband carried a heterozygous NPRL3 mutation (c.1545-1G>C, NM_001077350.3). Surprisingly, the mothers of the two probands each carried the variants, but neither had an attack. Bioinformatics analysis predicted that the mutation (c.954C>A) was in the highly conserved amino acid residues of NPRL3, which affected the α-helix of NPRL3 protein, leading to a truncated protein. The splice variant (c.1545-1G>C) resulted in the loss of the last exon of the NPRL3 gene. Conclusion: The results of this study provide a foundation for diagnosing NPRL3-related epilepsy by enriching their genotypes and phenotypes and help us identify the genetic etiologies of epilepsy in these two families.